Comparison of F-tests for Univariate and Multivariate Mixed-Effect Models in Genome-Wide Association Mapping - Onogi, Akio (Frontiers in Genetics, 2019)
Genome-wide association mapping (GWA) has been widely applied to a variety of species to identify genomic regions responsible for quantitative traits. The use of multivariate information could enhance the detection power of GWA. Although mixed-effect models are frequently used for GWA, the utility of F-tests for multivariate mixed-effect models is not well recognized. Thus, we compared the F-tests for univariate and multivariate mixed-effect models with simulations. The superiority of the multivariate F-test over the univariate test varied depending on three parameters: phenotypic correlation between variates (r), relative size of quantitative trait locus effects between variates (ad), and missing proportion of phenotypic records (mprop). Simulation results showed that, when mprop was low, the multivariate F-test outperformed the univariate test as r and ad differ, and as mprop increased, the multivariate F-test outperformed as ad increased. These observations were consistent with results of the analytical evaluation of the F-value. When mprop was at the maximum, i.e., when no individual had phenotypic values for multiple variates, as in the case of meta-analysis, the multivariate F-test gained more detection power as ad increased. Although using multivariate information in mixed-effect model contexts did not always ensure more detection power than with univariate tests, the multivariate F-test will be a method applied when multivariate data are available because it does not show inflation of signals and could lead to new findings.